Konsep Fitrah Dalam Hadis Nabi: Analisis Tekstual-Kontekstual Tentang Potensi Keimanan Sejak Lahir Dan Implikasinya Terhadap Pendidikan Islam Kontemporer - Istikhori Istikhori; Muhamad Naufal Firdaus; Amirulloh Amirulloh; Badru Salam; Ai Sundari; Siti Zainab; Opik Opik (Institute of Advanced Knowledge and Science, 2026)
This research examines the concept of fitrah in the hadith of Prophet Muhammad (peace be upon him) using a thematic hadith interpretation approach focused on textual and contextual analysis. The research aims to understand the nature of fitrah as an innate human potential and identify its implications for contemporary Islamic education systems. The research method employed is library research with content analysis techniques applied to authentic hadiths, particularly those narrated by Imam Bukhari and Muslim regarding the birth of children in a state of fitrah. The findings reveal that fitrah represents a natural disposition that Allah has instilled in every human being since birth, encompassing the inclination to recognize and worship Allah SWT as well as inherent potential for goodness. Chain of narration analysis demonstrates that hadiths concerning fitrah possess authentic quality with unbroken transmission chains and trustworthy narrators. This research discovers that although fitrah is universal, its development is significantly influenced by educational environments, particularly the family. Parents possess a determinant role in shaping children's religious identity through parenting patterns, exemplary conduct, and value cultivation. The pedagogical implications of the fitrah concept necessitate an integrated Islamic education system encompassing family, madrasah, and society to preserve and optimize children's fitrah development. This research recommends developing an Islamic education curriculum oriented toward awakening and actualizing fitrah, with humanistic teaching methods characterized by compassion and alignment with children's developmental stages.